Syntactic Perfective Aspect - محمد كمال خزعل (lark, 2019)
Abstract The purpose of this research is to examine the perfective aspect of linguistics, how it is used, and its importance in language. This research provided a more detailed explanation of the perfective aspect individually to understand it more comprehensively. This examination of the perfective aspect provided the basis on which the analysis occurred. This research analyzed the perfective aspect through its use in language. It is hoped that this explanation will provide greater inside into the identification of the perfective aspect and the usage of the perfective aspect in various languages as well as how it can be understood in English.